Application of fuzzy comprehensive evaluation method in the identification of potential faults of high-voltage power cables - Fu, Han; Ai, Yuhao; Qiu, Long; Ai, Yonghen; Yang, Bin; Shi, Yihui (Frontiers in Energy Research, 2024)
To identify the hidden faults in high-voltage power cables, a fuzzy comprehensive evaluation method is proposed. The suggested fuzzy comprehensive evaluation is completed in the following steps: by studying the actual high-voltage cable operations, it selects some relevant indices from operation monitoring data to form a comprehensive evaluation factor set, and then an evaluation set is established according to the corresponding operation guidelines. Subsequently, it utilizes the triangular distribution function to establish membership functions for calculating the cable fault evaluation set. The weights of evaluation factors are quantified using the analytical hierarchy process. It uses fault analysis of a city's 220 kV double-circuit cable system as an example to demonstrate that the proposed method can work effectively in fault identification, and can aid operation and maintenance personnel in providing valuable references.